2022
DOI: 10.1007/s00508-022-02046-7
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria and protozoa with pathogenic potential in Ixodes ricinus ticks in Viennese recreational areas

Abstract: SummaryIxodes ricinus is the most relevant vector for tick-borne diseases in Austria and responsible for the transmission of Borrelia burgdorferi sensu lato (s. l.), which causes Lyme borreliosis in humans; however, also other bacteria and protozoa can be found in ticks and have the potential of infecting people and animals. In this study we collected ticks in popular recreational areas in the city of Vienna in the years 2019 and 2020 and analyzed them for the presence of such putative pathogenic microorganism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The presented study revealed a zonal distribution of different spirochete species from the Borreliaceae family in Northern Poland not only by the presence or absence of particular species but also by differences in infection rates that correlate with different risks of human and animal infection. Similar differences in the distribution and infection rates are observed in other European studies [45][46][47]51,[58][59][60] but also in the case of different Borreliaceae species characteristics for Asia [61,62] and North America [63][64][65]. The cause of such zonality may be host specific, especially in the case of Borreliella species [66], and due to the differential availability in the studied area but not the climatic conditions which are similar for the entire area of research.…”
Section: Discussionsupporting
confidence: 79%
“…The presented study revealed a zonal distribution of different spirochete species from the Borreliaceae family in Northern Poland not only by the presence or absence of particular species but also by differences in infection rates that correlate with different risks of human and animal infection. Similar differences in the distribution and infection rates are observed in other European studies [45][46][47]51,[58][59][60] but also in the case of different Borreliaceae species characteristics for Asia [61,62] and North America [63][64][65]. The cause of such zonality may be host specific, especially in the case of Borreliella species [66], and due to the differential availability in the studied area but not the climatic conditions which are similar for the entire area of research.…”
Section: Discussionsupporting
confidence: 79%
“…The main vectors of B. miyamotoi differ in different countries, such as I. scapularis and I. pacificus in the United States, I. ricinus in Europe, I. persulcatus , I. ovatus, H. concinna and H. longicornis in China, I. persulcatus and I. pavlovski in Japan, I. ricinus and I. persulcatus in Russia [ 6 ]. An increasing number of B. miyamotoi strains in ixodid ticks have been identified in many countries including the Czech Republic, Egypt, and Austria [ [21] , [22] , [23] ]. Here, our study showed that R. microplus , I. ovatus , H. nepalensis and H. kolonini may be novel vectors of relapsing fever spirochetes in Yunnan province.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past three years, an increasing number of B. miyamotoi in ixodid ticks has been identified in many countries including the Czech Republic, Egypt, and Austria [ [21] , [22] , [23] ]. There has also been an increase in human infections in France, Austria, and Inner Mongolia Autonomous Region of China [ [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%